Evaluating Pulmonary Arterial Pressure in Angus Yearling Bulls at High Elevation: Associations with Birth Traits and Growth Performance - Kaylen Stearns; Hannah DelCurto-Wyffels; Sam Wyffels; Megan Van Emon; Noah G. Davis; Taylre Sitz; Tim DelCurto (Animals)
The objectives of this study were to model the relationship between pulmonary arterial pressure (PAP) estimates and birth weight, gestation length, and growth traits of developing bulls. Pulmonary arterial pressure estimates were collected from Angus yearling bulls ranging in age from 12 to 18 months from a Montana-based Angus operation (>1600 m elevation, 5406 yearlings/18-month-old bulls from 2016–2023). Pulmonary arterial pressure was positively correlated with birth weight (p < 0.01) and gestation length (p < 0.01). No relationship was observed between bull PAP and weaning weight (p = 0.26). Pulmonary arterial pressure scores were negatively correlated with yearling weight (p = 0.04). Additionally, PAP estimates were negatively correlated with birth-to-weaning gains (p < 0.01) and weaning-to-yearling gains (p = 0.02). Lastly, PAP scores were negatively correlated with birth to yearling growth (p < 0.01). Sire lines influenced offspring PAP scores (p < 0.01), and dam−sire lines tended to have an effect on offspring PAP scores (p = 0.09). In summary, PAP scores were related to birth weight, gestation length, yearling weight, and growth from birth to yearling age. Our findings suggest that selection for higher growth should also emphasize selecting for lower PAP scores.